Snort 2.0 intrusion detection - Beale, Jay.; Foster, James C. (Rockland, Mass. : Syngress ; Oxford : Elsevier Science, 2003)
The incredible low maintenance costs of Snort combined with its powerful security features make it one of the fastest growing IDSs within corporate IT departments. Snort 2.0 Intrusion Detection is the first book dealing with the Snort IDS and is written by a member of Snort.org. Readers will receive valuable insight to the code base of Snort and in-depth tutorials of complex installation, configuration, and troubleshooting scenarios. The primary reader will be an individual who has a working knowledge of the TCP/IP protocol, expertise in some arena of IT infrastructure, and is inquisitive about what has been attacking their IT network perimeter every 15 seconds. The most up-to-date and comprehensive coverage for Snort 2.0! Expert Advice from the Development Team and Step-by-Step Instructions for Installing, Configuring, and Troubleshooting the Snort 2.0 Intrusion Detection System Free CD Contains the Latest Version of Snort and Popular Plug-Ins Including ACID, Barnyard, and Swatch.
Includes index.
Keywords: Snort (Software); Intrusion detection systems (Computer security); Computer security; Electronic books